Implementasi Penanaman Nilai-Nilai Nasionalisme pada Siswa Sekolah Dasar melalui Pembelajaran IPS Materi Perkembangan Kemerdekaan Indonesia - Ayu Kartini; Isfi Aulia Septiani; Tin Rustini (Departement of Mathematics Education, 2024)
This article discusses the implementation of instilling nationalist values ​​in elementary school students through social studies learning with a focus on material on the development of Indonesian independence. This research aims to evaluate the effectiveness of learning methods in increasing students' understanding of the development of Indonesian independence and measuring its impact on the development of nationalist values. The research method uses a qualitative approach. The results of the research show that the implementation of nationalist values ​​can be applied by teachers in daily life at school. Effective learning methods can increase students' understanding of the development of Indonesian independence and significantly strengthen their nationalist values. This research provides guidance for educators in designing curricula that promote understanding of national history and shape students' characters with a strong spirit of patriotism and nationalism. Thus, implementing social studies learning with a focus on material on the development of Indonesian independence can play an important role in educating the younger generation who love and respect national values.